The effect of topography, tillage and stubble grazing on soil structure and organic carbon levels - Bricchi, E.=700 1 Formia, F.; Esposito, G.; Riberi, L.; Aquino, H.
(Es, En)
ilus., 55 ref.
Keywords: MATERIA ORGANICA; TOPOGRAFIA; TECNOLOGIA; LABRANZA; APLICACION DE ABONOS; ESPAÑA